STRESS GENERAL FACTORS OF THE PROFESSIONAL ENVIRONMENT IN TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Stressors in the personal and professional environment reduce the resilience of professionals and the vitality of the organization in which they work. Consequently, they force educators and organizational leaders to reckon with their presence.